2017
DOI: 10.1002/cne.24323
|View full text |Cite
|
Sign up to set email alerts
|

Cre‐expressing neurons in visual cortex of Ntsr1‐Cre GN220 mice are corticothalamic and are depolarized by acetylcholine

Abstract: The Ntsr1-Cre GN220 mouse expresses Cre-recombinase in corticothalamic (CT) neurons in neocortical layer 6. It is not known if the other major types of pyramidal neurons in this layer also express this enzyme. By electrophysiological recordings in slices and histological analysis of the uptake of retrogradely transported beads we show that Cre-positive neurons are CT and not corticocortical or corticoclaustral types. Furthermore, we show that Ntsr1-Cre-positive cells are immuno-positive for the nuclear transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 35 publications
11
34
0
Order By: Relevance
“…Together, the molecular and connectivity analysis of FOXP2-positive 119 neurons in layer 6 indicate that FOXP2 expression is highly enriched in CT neurons of primary 120 SSC during postnatal development. This is consistent with analysis in primary visual cortex of 121 adult mice, which showed that Foxp2/FOXP2 expression is nearly exclusive to Ntsr1-cre 122 expressing (CT) neurons in the adult (Tasic et al, 2016;Sundberg et al, 2018). The present 123 study builds on previous findings by demonstrating minimal colocalization with two layer 6 CC 124 markers (MET and CCK).…”
supporting
confidence: 87%
“…Together, the molecular and connectivity analysis of FOXP2-positive 119 neurons in layer 6 indicate that FOXP2 expression is highly enriched in CT neurons of primary 120 SSC during postnatal development. This is consistent with analysis in primary visual cortex of 121 adult mice, which showed that Foxp2/FOXP2 expression is nearly exclusive to Ntsr1-cre 122 expressing (CT) neurons in the adult (Tasic et al, 2016;Sundberg et al, 2018). The present 123 study builds on previous findings by demonstrating minimal colocalization with two layer 6 CC 124 markers (MET and CCK).…”
supporting
confidence: 87%
“…Investigating how their activity related to arousal level, we found that in the dark, spontaneous population activity of NTSR1 -positive CT neurons was strongly positively correlated with the arousal level of the mouse. Given that these NTSR1 -positive CT neurons are known to be directly depolarized and potently modulated by acetylcholine 41 , in the absence of visual inputs the spontaneous activity that we observed in the dark was likely strongly modulated and/or driven by the cholinergic inputs into V1. Upon drifting grating stimulation, CT population activity correlation with arousal became significantly less than in the dark, possibly because the strong visual inputs that they received from local V1 neurons reduced the influence of and thus the correlation with cholinergic activity.…”
Section: Discussionmentioning
confidence: 84%
“…We next examined the cell types of Foxp2 and/or Ctip2 expressing cells in layer 6. Since previous retrograde tracing experiments indicated that corticothalamic projection neurons in layer 6 expressed Foxp2 in SCx (Sorensen et al, ) and VCx (Sundberg, Lindström, Sanchez, & Granseth, ) of ∼8‐week old mice, we wondered if this is also the case in young postnatal mice. We injected the Retrobeads into the thalamus at P1 and examined the labeled cells at P5.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis of retrograde tracing of corticothalamic neurons with the Retrobeads combined with Foxp2 immunostaining at P5 showed that the majority of the labeled cells was Foxp2 + in the three sensory cortexes. We are not aware of any report showing the proportion of Foxp2 + in corticothalamic neurons at this young age, but with about 8‐week old mice, about 30% of corticothalamic neurons expressed Foxp2 in S1 (Sorensen et al, ), and about 85% of corticothalamic neurons are expected to express Foxp2 as about 98% of Ntsr‐1 expressing cells was Foxp2 + , while about 87% of corticothalamic neurons expressed Ntsr‐1 (Sundberg et al, ). No such report on ACx is available yet, but the support comes from our observation that the Foxp2 + band in ACx radially extends dorso‐medially toward VCx in the same coronal sections, where a recent report in VCx indicated the Foxp2 + band likely represents layer 6 (Gray et al, ).…”
Section: Discussionmentioning
confidence: 98%